2007
DOI: 10.2353/ajpath.2007.061025
|View full text |Cite
|
Sign up to set email alerts
|

A Homeobox Gene Related to Drosophila Distal-Less Promotes Ovarian Tumorigenicity by Inducing Expression of Vascular Endothelial Growth Factor and Fibroblast Growth Factor-2

Abstract: Homeobox genes control developmental patterning and are increasingly being found to be deregulated in tumors. The DLX4 homeobox gene maps to the 17q21.3-q22 region that is amplified in some epithelial ovarian cancers. Because amplification of this region correlates with poor prognosis, we investigated whether DLX4 overexpression contributes to aggressive behavior of this disease. DLX4 was not detected in normal ovary and cystadenomas, whereas its expression in ovarian carcinomas was strongly associated with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 41 publications
1
61
1
Order By: Relevance
“…Previous studies have shown that DLX4 is upregulated in leukemia and lung, breast, ovarian and prostate cancers (2)(3)(4)(5). In the present study, seven paired HCC tissues were analyzed by qPCR and western blot to detect the expression status of DLX4.…”
Section: Dlx4 Is Downregulated In Hcc Tissues As Compared With the Admentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies have shown that DLX4 is upregulated in leukemia and lung, breast, ovarian and prostate cancers (2)(3)(4)(5). In the present study, seven paired HCC tissues were analyzed by qPCR and western blot to detect the expression status of DLX4.…”
Section: Dlx4 Is Downregulated In Hcc Tissues As Compared With the Admentioning
confidence: 88%
“…Although absent in the majority of normal adult tissues, DLX4 has been reported to be widely expressed in leukemia and lung, breast, ovarian and prostate cancers (2)(3)(4)(5). The expression of DLX4 mRNA has been shown to be significantly increased in tumors with lymph node metastasis and a high histological grade (6).…”
Section: Introductionmentioning
confidence: 99%
“…27 Aberrant expression of DLX family members has also been associated with breast, ovarian and lung cancer progression/invasiveness. [32][33][34] Previous studies have demonstrated that DLX1 negatively affects TGFb signaling by direct interactions with Smad4, 27 a key downstream effector of TGFb/BMP signaling. Interactions between Smads and HOX genes were also shown in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The American Cancer Society estimates that about 22,440 women will receive a new diagnosis of ovarian cancer in the USA in 2017 [48]. In Hara's study, 47% of the ovarian carcinoma cases were found to exhibit extensive BP1 expression [47]. The data showed that BP1 expression in ovarian carcinomas is strongly associated with high tumor grade and correlates with disease stage.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…In cancer, overexpression of VEGF has been shown to enhance metastasis due to angiogenesis. Overexpression of BP1 in ovarian cancer cells induces levels of VEGF and FGF-2, stimulates endothelial cell growth and leads to increased microvessel density in tumors, but it is not known whether BP1 protein directly activates FGF-2 transcription [47].…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%